Acute Biliary Stone-Induced Pancreatitis: The Outcomes of Early vs. Delayed Laparoscopic Cholecystectomy : Early Versus Delayed Cholecystectomy - Ahmad, Muhammad Shabbir; Mehmood, Saeed; Kareemullah, Muhammad; Rashid, Muhammad; Hameed, Babar; Imran, Hafiz Muhammad; Hamad Ullah, Rana (Pakistan Journal of Health Sciences, 2024)
Gallstones often lead to biliary pancreatitis. While the majority of individuals may only have minor symptoms, a small percentage (around 20%) will develop severe pancreatitis, which can lead to catastrophic problems if it occurs again. Objective: To determine patients who have acute pancreatitis caused by biliary stones and evaluate the results of laparoscopic cholecystectomy performed early versus delayed. Methods: Total 390 patients with acute biliary stone-induced pancreatitis were presented in this study. After getting informed written consent detailed demographics of enrolled cases were recorded. In the group I, laparoscopic cholecystectomy was done within 72 hours; in the group II, it was done later after 72hours. Post-operative outcomes were compared by using t-test and chi square test among both groups. Results: Among all, 216 (55.4%) were males and 174 (44.6%) were females. Majority of the cases 140 (35.9%) had age 41-50 years. Most common complication was abdomen pain in 340 (87.2%) cases. Compared to delayed surgery, early laparoscopic cholecystectomy had a lesser complication rate (p<0.04), a shorter inpatient stay (p<0.003), and a faster recovery time. The mortality rates of the two groups were comparable (p=0.001). Less recurrence rate was experienced with early laparoscopic cholecystectomy (p<0.002). Conclusions: Compared to a late cholecystectomy, an early one greatly reduces the likelihood of postoperative complications, recurrent biliary events, the length of operation, and the length of time the patient must remain in the hospital for treatment of acute biliary pancreatitis.